Karakteristik Pelet Kayu Alau Hasil Pencetakan Menggunakan Alat Pres Sederhana: Characteristics of Alau Wood Pellets Printed Using a Simple Press Tool - Alpian Alpian; Dhietya Alip Hutomo; Wahyu Supriyati; Eva Oktoberyani Christy; Penyang Penyang; Santosa Yulianto; Yanciluk Yanciluk; Gimson Luhan (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Conventional energy sources have negative impacts on the environment, therefore alternative renewable energy from biomass is needed. Biomass energy can be converted into solid fuel in the form of wood pellets. Wood pellets can reduce the use of conventional energy and can be produced from wood waste using environmentally friendly technology. Technology plays an important role in wood pellet production, in addition to raw material composition and processing methods. This study used three particle sizes and three holding times in the pelletizing process. The parameters tested were moisture content, density, tool effectiveness and efficiency, and pellet shape characteristics. The results showed that the moisture content of all treatments met the SNI 8021:2014 standard, while the density values did not meet the standard. The effectiveness and efficiency of The DIP1 pellet molding device were still relatively low in terms of production capacity and pellet quality, both macroscopically (shape) and microscopically (stored energy density). Keywords: biomass, wood pellets, alau wood, simple technology, pellet molding device